Multi jet fusion 3D printing of graphene oxide nanocomposites - Lim, Zheng Han (Nanyang Technological University, 2023)
Nanofillers can be advantageous to be incorporated in polymer materials for 3D printing techniques, such as Multi Jet Fusion (MJF) to expand the potential applicability of printed parts. As MJF uses a unique printing process which relies on dark fusing agent to selectively sinter white polymer powders through infrared radiation, graphene oxide (GO), a potential nanofiller, is unsuitable to be mixed into polymer powder for MJF printing due to its dark colour. Hence, this project explores the feasibility of the use of GO-based agents to be directly delivered to polymer powders as a way to print polymer/GO nanocomposites. In this project, two GO agents (GOAs) containing GO, water, 2-pyrrolidinone, Trizma® base, and sodium dodecyl sulfate, were formulated through an iterative process to achieve printability for thermal inkjet printheads. The GO agents were used to print TPU nanocomposite samples, which were compared to samples printed using the conventional MJF fusing agent (FA). When compared to samples printed using FA, samples printed using the GOA with a higher GO concentration showed a 12.5% increase in tensile strength, a 29.5% increase in elongation at break, and a 23.5% decrease in Young’s modulus. While samples printed using the GOA with a lower concentration showed a 2.5% increase in tensile strength and a 5.1% increase in elongation at break and a 33.8% decrease in Young’s modulus. Both types of samples printed with GOAs showed an improvement in thermal stability at low percentage weight lost and results from differential scanning calorimetry on samples did not show any significant changes in the thermal properties where changes in onset and peak temperatures are all only up to ~3 °C. All samples displayed electrically insulating properties. As it is possible to formulate GOAs with good printability which can be used to print samples that exhibit improvements in mechanical properties and thermal stability with no negative effects on thermal properties observed, the printing of polymer/GO nanocomposites with this technique is shown to be feasible. With further development of GOAs, it is expected that new methods can be established to provide users new options to easily print stronger end-use parts reinforced by GO nanofillers with the potential of tailorable tensile properties.